A model for industrial development of the federal region of Kurdistan: science and technology policy, instruments and institutions - Almas Heshmati (Institute for the Study of Labor (IZA), 2007)
This report introduces two of the most successful industrial development models of the modern time the Japanese as a leader and the South Korean as its follower. The objective is to review the industrialization process in these two economies which have served as a model for development in many newly industrialized economies. The experience gained from a review of the two models is used to investigate the current industrial development in the Federal Kurdistan Region. In particular the focus is initially on the identification of the current policy and institutions in the region. The conditions, potential and pitfalls are investigated and the resources available in the region and those needed are quantified and the gap estimated. Based on experience gained and available information, the strategy for development is designed and an optimal model for industrialization of the Kurdistan region is proposed. Major steps to be taken during the industrialization process are identified and described in detail. Discussion of the of the possible industrial policy instruments to improve security and self-sufficiency is followed by a presentation of infrastructure organizations and their cooperation to implement the industrialization policy. Industrial policy here involves the regional government's use of its authority and resources to administer policies that address the needs of specific sectors, industries or corporations with the aim of raising their survival, productivity and competitiveness.
Keywords: H54; 330; Industrial development; industrialization process; industrial policy; infrastructure; Kurdistan; Industrialisierungspolitik; Japanisch; Koreanisch; Industriepolitik; Forschungs- und Technologiepolitik; Institutionelle Infrastruktur; Kurdistan (Irak)